Representation of the East in Western Literature (A Critical Discourse Analysis of the Travelogue Eothen) - Salahshour, Neda; Salahshour, Farzad (Richtmann Publishing, 2012)
Representation in discourse is a constructed practice; that is, it is not neutral. Events and ideas are not transmittedneutrally as they were, because they have to pass through a medium with its own ideological filters. Critical discourse analysis(CDA) is a type of discourse analytical research that primarily studies the way social power abuse, dominance, and inequalityare enacted, reproduced, and resisted by text and talk in the social and political context. Edward Said’s book Orientalism (1976)focuses on how the East is represented by the West. He believes that during the process of representation, the Orient is alsoremade. He mentions a number of writers who he believes depict distorted images of the East in order to satiate their colonizingends among whom is Kingslake and his travel narrative Eothen (1844). Twenty seven pages from this travelogue have beentaken as the data of this research. The purpose was to reveal how the writer has tried to create a biased image of the Orient.The method applied was van Dijk’s ideological square which is used to reveal forms of positive self and negative other. Uponextracting these biased images, the rhetorical techniques used to create them were identified. Interestingly the findings suggestthat the travelogue was saturated with creations of binary oppositions revealing a biased and inaccurate description of the East.